Treatment of pressure gun fractures and release in the wild of a caracara (Caracara plancus) - Cassanego, Guilherme Rech [UNESP]; Rahal, Sheila Canevese [UNESP]; de Risso, Bruno Oliani [UNESP]; Pigatto, Anita Marchionatti [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Wiley, 2025)
Abstract This report aims to describe the treatment progression of a free‐living southern crested caracara ( Caracara plancus plancus ) with gunshot‐related fractures. Radiographic examination revealed a comminuted fracture in the mid‐diaphysis of the humerus with displaced fragments, a comminuted fracture of the proximal third of the radius shaft, and the presence of bullet fragments. The humerus fracture was immobilised using a unilateral Type Ia acrylic resin pin skeletal fixator, which was applied without exposing the fracture site and remained in place for 4 weeks. A figure‐of‐eight bandage was used to stabilise the radial fracture for 1 week. The largest bullet fragment was also removed. After implant removal, the bird underwent a rehabilitation protocol that included flight training. Although physical examination revealed no motion at the fracture site, the humerus fracture line remained visible 5 months post‐surgery. At that point, the bird was released into the wild, underscoring the importance of proper interventions for preserving native wildlife.